Does instruction of Integers subject with cartoons effect students' mathematics anxiety? - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2010)
The purpose of this research is to investigate the existence of The Effect of Instruction of Integers Subject with Cartoons on Students' Mathematics Anxiety. Research consists of a semi-experimental study which was performed on 61 students during 2007-2008. These students were in their 7(th) year of primary education in the city of Bolu. An experiment and a control group were used in the research. While acquisition of Integers was handled with traditional methods in control group, it was handled with the use of cartoons in the experiment group. The data acquired with The Mathematics Anxiety Rating Scale, which is used before and after the research, was evaluated with statistical analysis method. According to the acquired data, results showed that instructions accompanied with cartoons lessened students' mathematics anxiety than traditional instructional methods. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cartoon; mathematics anxiety; mathematics education; integers